The Comparative Study of Bilingualism in East and Southeast Asia - Thi-Nham Le (Tạp chí Khoa học Xã hội và Nhân văn (VNU Journal of Social Sciences and Humanities), 2026)
The comparative study of bilingualism in East (Taiwan) and Southeast Asia (Vietnam) includes two interrelated investigations. This study provides valuable insights into the processes of language and literacy development among children from minority groups and examine patterns of language acquisition within school-age populations in bilingual communities. The research contributes to a deeper understanding of how bilingualism affects educational outcomes in these distinct cultural and linguistic contexts. Study A involved in-depth interviews with 62 Vietnamese immigrant participants and aimed to explore their language learning experiences and related issues of adaptation to Taiwanese culture. Study B, which was located in the Thái-speaking district of Bá Thước in Thanh Hóa province, involved fieldwork that primarily focused on the development of bilingual children in first grade. In the Chinese-speaking community of Taiwan, evidence suggests that immigrant parents make significant progress in the second language learning of Chinese. In turn, first generation children appear to be making progress that is parallel to that of their Chinese native-speaking peers. Similarly, in the Thái-speaking communities, progress in mastering the national language, Vietnamese, as a second language is comparable to that in Vietnamese-speaking communities (Kinh monolingual children). Received 7th July 2024; Revised 25th August 2024; Accepted 15th September 2024